Model of Islamic Counseling in Developing Studentsâ Competencies in MAN 1 Bandung - Nursyamsi, Nursyamsi (AT-TALIM, 2015)
Studentsâ interpersonal problems with their peers, parents, and teachers have become more critical in the present society that serious attention must be paid to overcome it.Â  Therefore, Islamic counseling model which is derived from the Quranic principles has been developed to sustain the wealthy condition of individual students. The purpose of this research is to develop an effective Islamic counseling model that may increase studentsâ interpersonal competency inÂ  MAN I Bandung. Â To achieve such a purpose, then, a Research and Development (R&D) through need assessment, development, experiment, and model revise were set up.Â  A quasi â experiment with âPretest â Posttest Control Group Designsâ procedure has been implemented to test the model being developed. The finding showed that the level of studentâs interpersonal competency before the treatment varied greatly. The post-test score after the treatment, however, showed that their interpersonal competencies got significantly improved. This improvement suggests that studentâs interpersonal competency should be developed in terms of: self perceptive and other people, self firm, become comfortable with one self and other people, become independent person, realistic expectation to oneself and other people, and self protection in interpersonal situations.Keywords: Â Â Islamic Counseling Model and Interpersonal CompetencyCopyright Â© 2015 by Al-Talim All right reserved